COVID-19-Associated Ischemic Colitis: A Rare Manifestation of COVID-19 Infection-Case Report and Review - Dustin J. Uhlenhopp DO; Rajarajeshwari Ramachandran MD; Eric Then MD; Swetha Parvataneni MD; Tyler Grantham MD; Vinaya Gaduputi MD, FACP (SAGE Publishing, 2022)
Following the first report of COVID-19 infection in December 2019 as a respiratory illness, it has proven to be a multisystem disease. There are few reported cases of ischemic colitis with COVID-19 infection in the medical literature to date and we have limited understanding of its pathophysiology. We report 2 cases of ischemic colitis as the only manifestation of COVID-19. In addition, we review the current limited literature regarding COVID-19-associated ischemic colitis.